2021
DOI: 10.1038/s41598-021-89563-z
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of altruistic punishments among heterogeneous conditional cooperators

Abstract: It has been known that altruistic punishments solve the free rider problem in public goods games. Considering spatial structure and considering pure strategies significant advances have been made in understanding the evolution of altruistic punishments. However, these models have not considered key behavior regularities observed in experimental and field settings, where the individuals behave like conditional cooperators who are more willing to donate and are also more willing to punish free riders. Considerin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…As far as altruistic punishment is concerned, it is ineffective when the possibility arises for punishing the cooperators, e.g., due to bribery 42 or imperfect information 43 . Moreover, this mechanism does not distinguish between those who free ride due to selfish interests and those who free ride only because others are doing so 44 . Overall, punishment can override altruistic motives, leading individuals to free ride as soon as the opportunity arises to evade punishment 45 47 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as altruistic punishment is concerned, it is ineffective when the possibility arises for punishing the cooperators, e.g., due to bribery 42 or imperfect information 43 . Moreover, this mechanism does not distinguish between those who free ride due to selfish interests and those who free ride only because others are doing so 44 . Overall, punishment can override altruistic motives, leading individuals to free ride as soon as the opportunity arises to evade punishment 45 47 .…”
Section: Introductionmentioning
confidence: 99%
“…Our novel alternative to punishment builds on the reciprocal nature of the trust—the fact that people reciprocate voluntary trust 68 —as well as the conditional nature of human cooperation—the fact that negative reciprocity can be switched to positive reciprocity given sufficient cooperation levels 44 , 69 71 . More specifically, it has been observed that most people reciprocate trust when the initial act of trust is taken voluntarily 68 , e.g., as is the case with successful business organizations who foster a culture of trust by placing trust in others 72 – 74 .…”
Section: Introductionmentioning
confidence: 99%
“…In collective scenarios 4 , 8 , 10 , 40 , 58 – 60 , such as social dilemmas 5 , 6 , 8 , the second approach emphasizes the inherent altruistic nature of human behavior 61 71 , explicitly highlighting concepts such as reciprocity, fairness, and retaliation 72 . Several significant models rooted in reciprocity have been proposed elsewhere 73 .…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of the conditional nature of cooperation, theoretical examinations 68 , 86 89 and experimental investigations have explored conditional cooperation 11 , 90 – 93 . The author of this paper has undertaken a comprehensive analysis of the evolution of conditional cooperation, considering various scenarios, for example, by scrutinizing a wide array of imitation strategies (Battu 71 ; Battu et al 70 ; Battu and Rahwan 68 ; Battu and Srinivasan 69 ). In this context, individuals tend to emulate those who not only achieve higher payoffs but also enjoy a superior reputation.…”
Section: Introductionmentioning
confidence: 99%